(untitled) (Journal of Scientific Research, 2014)
In the present investigation, an attempt was made to develop gastro retentive tablets of cefpodoxime proxetil (CP) using locust bean gum as release retarded material. CP is an orally administered, extended spectrum, semi-synthetic antibiotic of cephalosporin class. CP has a short elimination half-life and also possesses high solubility, chemical, enzymatic stability and absorption profiles in acidic pH which makes CP suitable candidate for formulating it as gastro retentive dosage form for improved bioavailability. Sodium bicarbonate and citric acid were used as effervescent agents to get desired floating properties. The tablets prepared were evaluated and found to have acceptable physicochemical properties. The in vitro release data of optimized formulation was treated with mathematical equations and was concluded that drug release followed zero order kinetics with anomalous transport mechanism. Based on the results it can be concluded that floating tablets of cefpodoxime proxetil containing locust bean gum provides a better option for controlled release action and improved bioavailability. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.18339 J. Sci. Res. 6 (3), 563-579 (2014)